2021
DOI: 10.3390/cancers13020257
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of miR-181b in B Cells of CLL Improves the Anti-Tumor Cytotoxic T Cell Response

Abstract: The clinical progression of B cell chronic lymphocytic leukemia (CLL) is associated with immune cell dysfunction and a strong decrease of miR-181b-5p (miR-181b), promoting the death of CLL cells. Here we investigated whether the reduction of miR-181b impairs the immune response in CLL. We demonstrate that activated CD4+ T cells increase miR-181b expression in CLL through CD40–CD40L signaling, which enhances the maturation and activity of cytotoxic T cells and, consequently, the apoptotic response of CLL cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The previous studies indicated that the miRNA-mediated effects depend on specific cell types and cellular context [23,24]. miR-181b was identified as regulating B cell differentiation and facilitating the maturation of cytotoxic T cells [25]. Indeed, miR-181b has been detected in many cancers, including breast cancer, pancreatic and gallbladder cancer, glioblastoma multiforme, and chronic lymphocytic leukemia [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies indicated that the miRNA-mediated effects depend on specific cell types and cellular context [23,24]. miR-181b was identified as regulating B cell differentiation and facilitating the maturation of cytotoxic T cells [25]. Indeed, miR-181b has been detected in many cancers, including breast cancer, pancreatic and gallbladder cancer, glioblastoma multiforme, and chronic lymphocytic leukemia [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…miR-181b was identified as regulating B cell differentiation and facilitating the maturation of cytotoxic T cells [25]. Indeed, miR-181b has been detected in many cancers, including breast cancer, pancreatic and gallbladder cancer, glioblastoma multiforme, and chronic lymphocytic leukemia [25][26][27][28][29]. Moreover, several studies revealed that miR-181b could inhibit vascular inflammation and the initiation and progression of atherosclerosis [13,30].…”
Section: Discussionmentioning
confidence: 99%
“…Other miRNAs involved in chemoresistance are miR-181a and miR-181b. Studies have evidenced that in aggressive CLL cases, the expression of miR-181b was decreased while conversely, the expression of this miRNA was constant in stable conditions of the disease [164,165]. In fact, miR-181b increased susceptibility to chemotherapy by targeting the 3'UTR region of the anti-apoptotic BCL-2 gene [166].…”
Section: Mirnas As Important Targets In Cll Treatmentmentioning
confidence: 99%
“…Exosomes released in T-cell leukemia are implicated in the suppression of specific immune cells via the impairment of Treg and NK cell functions by miR-150 and miR-181 [180]. Overexpression of miR-181b in B-cells of chronic lymphocytic leukemia (CLL) resulted in an improved antitumor response of cytotoxic T-cells [181]. Overexpression of miR-195 in a human diffuse large B-cell lymphoma (DLBCL) cell line attenuated the immune escape of transformed cells by targeting PD-L1 [182].…”
Section: Hematological Malignanciesmentioning
confidence: 99%